Jogos digitais como objeto de aprendizagem: a questão da intenção pedagógica - Silva, Thaís Alves da (2020)
The approach of this research falls on the Learning Objects, in the context of distance education, and on the methods of analysis and evaluation of the pedagogical aspects of the Learning Objects. The research consists in analyzing and describing if there are pedagogical aspects and intentionality in the Learning Objects. The type of study object of the research is a game, and it seeks to analyze how the construction and development of this game takes place and the pedagogical intention of this object. The objective of the research falls on the analysis of the pedagogical intention of a game. The proposal is to research methods with criteria for the evaluation of Learning Objects and to present them. At last, choose one of them for use, in the dissertation methodology, which will also be descriptive. I will use the LORI method, among all types of criteria and evaluation parameters of objects. The methods found are interesting, and very close to each other, therefore, LORI was chosen as the method to be applied in the game analysis. It was developed to make evaluations of the pedagogical aspects of the objects, like the others, but, due to the proximity of what is intended in this research, it was the chosen one. By means of this method, I will make an analysis and description of the game, and the methodology of this research will be based on a description, also, of the whole process of analysis of the game, based on the criteria established by the LORI method. The expected results with these analyses are to identify if there are pedagogical aspects in the Learning Objects, more objectively in the games. Present the evaluation criteria for the LOs and adapt the existing checklist models for the instructional designer's area, and, with that, help for the development of Learning Objects with their pedagogical intention more apparent and clearer to the user